Forming Conscious Discipline Among Students of Higher Educational Institutions - Safonova, Oksana Vladimirovna (2021)
The article deals with forming conscious discipline among students of higher educational institutions, as well as defines the criteria for assessing the development of discipline. The research object of the present work is the process of educating conscious discipline among students of higher educational institutions. The authors used the following methods in the article. Firstly, the analysis of literature sources made it possible to single out the main theories that were taken as the basis for the study. Secondly, the surbey method of conversation allowed the authors to identify the main problems of the relationship between students and teachers, as well as the reasons for the violation of discipline. Thirdly, the authors used the observation method, which helped to determine the relationship and actions of students in the group. This made it possible to more objectively identify the causes of conflicts and develop proposals for their resolution. The authors also studied special methodological literature on improving student discipline, which allowed them to propose measures to increase students’ motivation in the formation of conscious discipline. According to the authors, purposefulness, objectivity and pedagogically expedient actions of teachers, and their communication with students are the leading conditions that ensure the parenting of conscious discipline.